JURIDICAL ANALYSIS OF LIFE INSURANCE COMPANIES' BAD FAITH ON INSURANCE POLICIES RELATED TO CLAIM PAYMENT OBLIGATIONS - Teuku Daudsyah; Herlina Hanum Harahap; Muhammad Ansori Lubis (LPPM YPITI, 2026)
The principle of utmost good faith is the most important principle in life insurance contracts. This principle is applied in life insurance practice, among other things, when the insured completes the insurance application form. The legal protection provided to consumers in life insurance businesses in Indonesia is based on the principle of utmost good faith, which is the act of accurately providing all requested and unsolicited information from the insurance company regarding the insured item or the insured object/interest. Examples of bad faith by life insurance companies regarding life insurance policies related to their obligations in running the life insurance business include the insurer's frequent refusal to pay life insurance claims.